IMPLEMENTASI PROGRAM PROLANIS STUDI KASUS DI UPT PUSKESMAS SAITNIHUTA KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN - Bertua SM Siregar; Donal Nababan; Frida Lina Tarigan; Wisnu Hidayat; Evawani Silitonga (Universitas Pahlawan, 2022)
In order to improve the health status of the community, as well as the success of the social security program in the health sector, BPJS Health guarantees promotive and preventive services for individual participants. One of them includes improving health for participants with chronic diseases. The purpose of this study is to describe and explain the implementation of the Prolanis Program at Saitnihuta Health Centre, Doloksanggul District, Humbang Hasundutan Regency in 2022. This research is a qualitative research, through in-depth interviews with informants. The informants in this study were 10 people consisting of the Head of the Health Center, JKN Treasurer, P-Care Officer, Implementer of the Prolanis Program, Doctor in Charge of Prolanis, Drug Manager, Posbindu Cadre, DM prolanis participant and hypertension prolanis participant (2 people). Methods of collecting data with primary data through in-depth interviews and secondary data through documents, literature, previous research journals. The process of data analysis is carried out by means of data reduction, data presentation and drawing conclusions and verification. The results showed that from the input elements (man, money, method and material), it is known that p-care officers have not received training, there is no clear job description between p-care officers and prolanis officers, there is no budget allocation for financing prolanis activities, the lack of tables and chairs, as well as internet network disturbances during the prolanis activity. From the element of the process, that the prolanis activities have been carried out in accordance with existing regulations. Meanwhile, from the output element, that the achievement of the RPPT indicators has not been achieved, even though the health monitoring of prolanis has been going well, even the health center always set targets by exceeding the targets set by BPJS. The conclusion is that the implementation of the prolanis program has been good, but the RPPT indicators have not been achieved. This happens because of confusion and obstacles in the data entry process. It is hoped that BPJS Health will disseminate information to health workers at the Saitnihuta Health Center, especially the Prolanis management team, regarding the concept of implementing Prolanis, so that the program can run according to existing regulations, and provide services proactively to Prolanis participants.